Obstacles to the Implementation of clinical practice guidelines at Mandau District General Hospital. - Zelvia, Sindy; Nasution, Sri Wahyuni; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Folia Medica Indonesiana, 2024)
Highlights: 1. Given the suboptimal implementation of clinical practice guidelines at Mandau District General Hospital, it is important to conduct research on potential obstacles to this problem. 2. The findings of this study can encourage hospitals to develop and apply effective clinical practice guidelines while also addressing the obstacles to their implementation. Abstract Clinical practice guidelines are procedures followed by physicians to optimize healthcare services and achieve more effective outcomes. Conducted in October 2022, this study aimed to analyze the factors that hinder the implementation of clinical practice guidelines among physicians at Mandau District General Hospital, Bengkalis, Indonesia. This study used an analytical survey design and a cross-sectional approach. This study included all 85 individuals who were employed as general practitioners at the Mandau District General Hospital. The data were subjected to univariate, bivariate, and multivariate analyses. The independent t-test was used in the data analysis, with a value of p<0.05 considered significant. The results showed that there was an association between the implementation of clinical practice guidelines and several variables, including the levels of ability in recognizing and explaining clinical pictures of diseases (p=0.008), diagnosing diseases (p=0.004), carrying out initial management (p=0.000), and carrying out independent and directed management (p=0.001). Upon conducting the follow-up analysis on logistic regression, it was found that the variables that were associated with the implementation of clinical practice guidelines were the ability to carry out initial management (p=0.000, OR=65.512, 95% CI=22.048–98.835). In conclusion, physicians' insufficient ability to perform initial management hinders the implementation of clinical practice guidelines. This study suggests incorporating the findings as input in the evaluation and development of training for physicians on the implementation of clinical practice guidelines.